Bibliometric review of augmented reality in education - Lorenzo Lledó, Gonzalo; Scagliarini Galiano, Christina (Revista General de Información y Documentación, 2018)
Education is one of the basic support of today’s societies. There are many tools to improve the quality of educational processes. One of the new instruments being applied in recent years is augmented reality. Therefore, the aim of this research was to obtain a review of the state of scientific production on augmented reality in Education. To do this, it has been worked with the advanced search tab of the Web of Science. After that, it was achieved a sample of 347 articles that were analyzed according to a series of bibliometric indicators. The results indicate that the vast majority of journals are included in the Emerging Citation Index; however, the authors often publish in JCR journals (q3). In the same way, authors tend to cite more often those articles that come from years with little scientific production. In the same way, Spain is the largest producer of articles and has a high expansion rate due to its low isolation rate. Finally, the 2015-2017 period has been the highest year’s production. Future research will consider analyzing which topics have been studied on and the systems applied.